The Effect of Using Acidified Imperata cylindrica as a Co-substrate with Dairy Cow Manure on the Digesters Performance - A. R. Mustikasari; S. Sutaryo; N. Ufidiyati; A. Purnomoadi (Tropical Animal Science Journal, 2023)
The objective of the current study was to examine the effect of the utilization of acidified cogon grass (CG) (Imperata cylindrica) as a co-substrate for the anaerobic digestion of dairy cow manure (DCM). Four continuous stirred-tank reactor (CSTR) digesters with various substrate compositions, namely, T1 (100% DCM), T2 (95% DCM and 5% CG), T3 (95% DCM and 5% acidified CG using 4% H2SO4 solution), and T4 (95% DCM and 5% acidified CG using Wuluh star fruit (Averrhoa bilimbi L) filtrate), were operated. This study was conducted for 66 d or 3 hydraulic retention times (HRTs). Also, it evaluated the methane production of the digested slurry of each CSTR digester (batch-type) with five replications in each treatment. The results indicated that the methane production in T2, T3, and T4 in the unit of L/kg substrate increased by 35.52%, 41.95%, and 45.44%, respectively, compared with that in T1. Furthermore, the productions in T3 and T4 increased by 4.35% and 7.25%, respectively, compared with that in T2. The production from the slurries of CSTR digesters in units of L/kg substrate and L/kg volatile solid (VS) showed significantly different results (p<0.05). A neutral pH value was maintained so the anaerobic digestion process could occur optimally. The total ammonia nitrogen concentrations were low, and the volatile fatty acid concentrations were not significantly different (p>0.05). Therefore, with or without acidification, CG can be used as a co-substrate with DCM to enhance methane production.